Emily Bagguley PhD - Gill, Philip; Bagguley, Emily; Kister, Guillaume; Moniruzzaman, Monir (Cranfield University, 2018)
Solid Composite Propellants for Improved Safety and Mechanical Properties This work looks to optimise and develop novel composite propellant formulations for use in unconventional rocket motor designs, in particular an integrated ramjet rocket motor. The particular design constraints of such a motor require that the booster propellant, required to get the rocket motor up to operational speed, use the same nozzle as the sustainer propellant and as a result must have the same operational requirements such as low pressure (1.5-2 MPa compared to ~10MPa for conventional rocket motors). In simple terms, this work aims to develop an extremely high burn rate propellant which works at extremely low pressures.
Keywords: 'PhD'; 'Resonant acoustic mixing'; 'RAM'; 'Propellants'; 'Chemical Thermodynamics and Energetics'